Usulan Redesain Bak Pencucian Ubi dengan Pendekatan Antropometri Guna Mengurangi Beban Kerja Fisik (Studi Kasus : UD. Rezeki Baru) - Sari, Budi Try; Andriani, Meri; Dewiyana, Dewiyana (Institut Teknologi Adhi Tama Surabaya, 2024)
UD. Rezeki Baru is a micro business engaged in the snack industry. In the production process, workers experience fatigue seen from the activities of workers who complain of pain in the muscles with a bent position. The purpose of this study is to identify the physical workload and provide a proposal for the dimension size of the ergonomic washing tub redesign. The methods used are cardiovascular load to identify physical workload and anthropometric approach to provide proposals for improving the dimension size of ergonomic washing tub redesign. Results and discussion, cardiovascular load in the morning 4 workers experienced